Modrna engineered artificial skin grafts and uses

CN117045866BActive Publication Date: 2026-10-13SHANGHAI MURDOCH BIO TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310648627.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2026-10-13
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

[0004]然而,目前未见利用modRNA技术结合复合纳米纤维膜和HFFs开发具有功能的人工真皮移植物的报道

Benefits of technology

[0017]本发明的有益效果在于:本发明旨在利用modRNA技术结合复合纳米纤维膜和HFFs开发具有功能的人工真皮移植物。在利用HFFs和电纺复合纳米纤维膜构建人工真皮(AD)基础上,使用VEGFA modRNA对其改造,并进行小鼠全层皮损的移植修复实验,通过伤口面积的变化和组织学染色来评估其疗效、存活率及血管生成情况。结果发现复合纳米纤维膜接种成纤维细胞并经培养后再转染modRNA,可以有效促进伤口愈合,具有修复速度快、移植物成活率高、细胞存活率高、血管化效率高的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117045866B_ABST
    Figure CN117045866B_ABST
Patent Text Reader

Abstract

The application relates to a modRNA modified artificial skin patch and application. The base material of the artificial skin patch is a nanofiber membrane, the nanofiber membrane is loaded with fibroblasts, and the fibroblasts are transfected with modRNA. The artificial skin patch prepared by the application has the advantages of high repair speed, high graft survival rate, high cell survival rate and high vascularization efficiency for wound treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedicine, specifically to a modRNA-modified artificial skin graft and its applications. Background Technology

[0002] Acute or chronic skin injuries caused by external factors or diseases seriously threaten patients' lives, health, and quality of life. [1] Although the skin has some self-repairing ability, large and deep wounds must be treated to effectively prevent infection, promote skin repair, and avoid scarring. [2-3] Currently, clinical repair of skin defects mainly includes methods such as autologous skin transplantation, allogeneic skin transplantation, xenogeneic skin transplantation, or other skin substitutes. [4] Autologous skin transplantation is limited by the availability of tissue, while allogeneic or xenotransplantation is subject to ethical and safety constraints. The development of skin tissue engineering has provided new solutions for the repair of large-area skin tissue defects. [5] Although tissue-engineered skin has been commercialized and applied clinically, its vascularization has not yet been fully realized, which is one of the key issues hindering its development. Currently, research on the vascularization of tissue-engineered skin mainly focuses on using various angiogenic cells, recombinant growth factors, gene transfection technology, and novel biomimetic scaffolds to promote angiogenesis. However, each method has its limitations and cannot perfectly solve the problem of vascularization in tissue-engineered skin. [6-8] Promoting angiogenesis and accelerating the vascularization of tissue-engineered skin have always been hot topics in skin tissue engineering research.

[0003] Chemically synthesized modified messenger RNA (modRNA) is a novel protein expression technology that has gained international popularity in recent years. It involves chemically modifying in vitro synthesized mRNA at the nucleotide level to achieve transient, local, and efficient expression of target proteins in tissues or cells in vivo, thereby achieving therapeutic effects. [9-11] Compared to traditional plasmids or viral gene vectors, modRNAs have unique advantages: they can function without entering the nucleus, have a low risk of integration into the host genome, and are highly safe; they are controllable, enabling short-term, pulsed expression of the target protein; and after structural modification and base modification, they exhibit good stability, low immunogenicity, and efficient protein translation capabilities.

[12] In the field of tissue regeneration, there are also studies using modRNAs encoding VEGFA for therapeutic purposes. For example, Chien et al. [13,14] We pioneered the preparation of VEGFA into modRNA for direct in vivo injection, and found it to have a significant therapeutic effect on myocardial infarction. Previously, Yu et al. from our research group...

[15] It was found that treatment after VEGFAmodRNA transfection of cells can effectively prevent lower limb ischemia and necrosis and promote angiogenesis and muscle regeneration.

[0004] However, there are currently no reports of developing functional artificial dermal grafts using modRNA technology combined with composite nanofiber membranes and HFFs. Summary of the Invention

[0005] The purpose of this invention is to provide a modRNA-modified artificial skin graft, wherein the substrate of the artificial skin graft is a nanofiber membrane, the nanofiber membrane is loaded with fibroblasts, and the fibroblasts are transfected with modRNA.

[0006] In one embodiment of the present invention, the nanofiber membrane is a composite nanofiber membrane prepared by one or two of collagen and gelatin with poly(L-lactide-caprolactone).

[0007] As a preferred example, the mass percentage of poly-L-lactide-caprolactone in the composite nanofiber membrane is 40%-60%.

[0008] As another preferred example, the composite nanofiber membrane is made of collagen and poly(L-lactide-caprolactone). More preferably, the collagen accounts for 40%-60% by mass.

[0009] In another embodiment of the present invention, the composite nanofiber membrane is prepared by electrospinning.

[0010] In another embodiment of the present invention, the fibroblasts are human foreskin fibroblasts.

[0011] In another embodiment of the present invention, the modRNA is VEGFA, PDGF, TGF, FGF, EGF, IGF or SDF-1α modRNA.

[0012] The present invention also provides a method for preparing any of the above-mentioned artificial skin grafts, comprising the following steps:

[0013] A) Preparation of nanofiber membranes;

[0014] B) Seed fibroblasts into the nanofiber membrane and culture them;

[0015] C) Perform modRNA transfection.

[0016] The present invention also provides the use of any of the above-mentioned artificial skin grafts in the preparation of products for repairing wounds caused by acute or chronic skin injuries.

[0017] The beneficial effects of this invention are as follows: This invention aims to develop functional artificial dermal grafts using modRNA technology combined with composite nanofiber membranes and HFFs. Based on the construction of artificial dermis (AD) using HFFs and electrospun composite nanofiber membranes, VEGFA modRNA was used to modify it, and transplantation and repair experiments were conducted on full-thickness skin lesions in mice. The efficacy, survival rate, and angiogenesis were evaluated by changes in wound area and histological staining. The results showed that inoculating fibroblasts with the composite nanofiber membrane, followed by culture and transfection with modRNA, effectively promoted wound healing, exhibiting advantages such as rapid repair speed, high graft survival rate, high cell survival rate, and high vascularization efficiency. Attached Figure Description

[0018] Figure 1 Scanning electron microscopy (SEM) images and diameter distributions of the composite nanofiber membranes in each group. AC, GI: SEM images (bar = 5 μm) of different composite nanofiber membranes (A: 0% BC, B: 10% BC, C: 20% BC, G: 30% BC, H: 40% BC, I: 50% BC); DF, JL: Diameter distribution of nanofiber membranes in different groups (D: 0% BC, E: 10% BC, F: 20% BC, J: 30% BC, K: 40% BC, L: 50% BC).

[0019] Figure 2 Mechanical property analysis of each group of composite nanofiber membranes. AD: Stress-strain curves (A: dry, C: wet) and Young's modulus (B: dry, D: wet) of the six groups of nanofiber membranes.

[0020] Figure 3 XRD and FTIR composition determination of composite nanofiber membranes. A: XRD patterns of each group of composite nanofiber membranes; B: FTIR spectra of each group of composite nanofiber membranes.

[0021] Figure 4 Staining of HFFs on composite nanofiber membranes for dead / live cells. A: Staining of HFFs on composite nanofiber membranes 24 h after inoculation: green represents AM (live cells); red represents PI (dead cells) (bar = 200 μm); B: Quantitative analysis of the staining results.

[0022] Figure 5 Skeletal staining of HFFs cultured on nanofiber membranes for 1 and 3 days (bar = 100 μm).

[0023] Figure 6 The proliferation of HFFs cultured on nanofiber membranes for 1, 3, and 5 days in each group.

[0024] Figure 7Construction of artificial dermis in vitro. A: HE staining of artificial dermis of different thicknesses (bar = 200 μm); B: Quantitative analysis of artificial dermis thickness (0.5M: 0.5 x 10⁻⁶). 6 1M: 1.0x10 6 3M: 3.0x10 6 6M: 6.0x10 6 ).

[0025] Figure 8 Expression and efficiency of GFP modRNA transfection in AD. A: Expression of GFP protein at different time points after GFP modRNA transfection in AD (bar = 200 μm); B: Flow cytometry analysis of transfection efficiency of GFP modRNA in AD 24 h after transfection.

[0026] Figure 9 VEGFA protein secretion after AD transfection. A: New VEGFA secretion at different time points after AD transfection with VEGFA modRNA; B: Cumulative VEGFA secretion at different time points after AD transfection with VEGFA modRNA.

[0027] Figure 10 VEGFA in AD transfection supernatant promotes HUVECs to form tubular structures. A: VEGFA in AD transfection supernatant promotes the formation of small tubular structures of HUVECs (bar = 200 μm); B: Statistical graph of the number of small tubules formed in the control group and experimental group.

[0028] Figure 11 The effect of VEGFA on the proliferation and migration of HUVECs in the supernatant after transfection with AD. A: The effect of VEGFA on the proliferation and migration of HUVECs in the supernatant after transfection with AD (bar = 200 μm); B: Statistical graph of scratch healing in the control group and the experimental group.

[0029] Figure 12 Effects of different interventions on wound healing in mice. A: General images of wound healing in each group on days 0, 4, and 10; B: Statistical analysis of wound area in each group at different time points.

[0030] Figure 13 Morphological staining of each group after lesion healing. AB: (A) HE staining and (B) Masson staining (bar = 150 μm) of the non-traumatic group and each wound group on day 10.

[0031] Figure 14 Survival status of artificial dermis after in vivo transplantation. A: Immunofluorescence staining of Lamin A+C in skin wound tissue on day 10 post-treatment (bar = 150 μm); B: Quantitative analysis of AD cell survival on day 10 post-treatment.

[0032] Figure 15 Angiogenesis in the wound healing area of ​​each group. A: CD31 immunofluorescence staining of skin wound tissue on day 10 after treatment (bar = 150 μm); B: Quantitative analysis of CD31 positive capillary density in each group.

[0033] Figure 16 Schematic diagram of VEGFA modRNA-modified AD for treating mouse skin lesions. A: In vitro construction and modification of artificial dermis; B: In vivo treatment of mouse skin lesions with VEGFA-modified AD. Detailed Implementation

[0034] The following examples are provided to help better understand the present invention, but are not intended to limit the invention.

[0035] Example 1

[0036] 1. Materials and Methods

[0037] 1.1 Preparation of collagen / gelatin / PLCL composite nanofiber membrane

[0038] Composite nanofiber membranes were prepared using BC (type I collagen, C9879-1G, Sigma, Germany), GEL (gelatin, 48722-100G, Sigma, Germany), and PLCL (poly(L-lactide-caprolactone, LA:CL = 50:50; Mn: 450000, Jinan Daigang Biotechnology) at different mass ratios (BC / GEL / PLCL = 0:50:50, 10:40:50, 20:30:50, 30:20:50, 40:10:50, 50:0:50; corresponding to 0% BC group, 10% BC group, 20% BC group, 30% BC group, 40% BC group, and 50% BC group, respectively). The membranes were stirred with a magnetic stirrer for 72 hours until fully dissolved, and then electrospun. The solution was injected into a 10ml syringe using a blunt needle and then pumped to the electrospinning apparatus (TXR1020N30-30, Teslaman, China) at a rate of 1ml / h, a voltage of 11–13kV, and a distance of 12cm using a syringe pump (KDS100, KDS Scientific, USA). More detailed electrospinning parameters are shown in Table 1. The obtained nanofiber membranes were dried in a vacuum oven for one week to remove residual solvent before use in subsequent experiments.

[0039] Table 1 Electrospinning parameters

[0040]

[0041] (Abbreviations: PLCL, poly-L-lactic acid-co-ε-caprolactone; GEL, gelatin; BC, bovine Achilles tendon collagen)

[0042] 1.2 Characterization of composite nanofiber membranes

[0043] Scanning electron microscopy (SEM): After vacuum drying, the nanofibers were sprayed at an accelerating voltage of 20 kV for 45 seconds, and their microstructure and surface morphology were observed using a scanning electron microscope (SEM) (ZEISSMERLINcompat, ZEISSco. Ltd., Germany). The obtained SEM images were processed using Image-proplus 6.0 software. At least 100 nanofibers were randomly selected from different SEM images of each sample for measurement; the fiber diameter is expressed as (mean ± standard deviation).

[0044] Mechanical properties: After vacuum drying, the dry mechanical properties of the membrane were tested using a benchtop uniaxial tensile testing machine (Model 3344, Instron, USA). The sample size was 10 cm x 1 cm, and the elongation was 5 mm / min. Curves were created using Graph-PadPrism software. The dry membrane was then immersed in distilled water for 30 min, and its wet mechanical properties were tested using the same method. Six samples were tested in each dry / wet test group.

[0045] Compositional analysis: XRD analysis of the nanofiber membrane was performed using an XRD diffractometer (D8 ADVANCE, Bruker, Germany) at a tube voltage of 40 kV, a tube flow rate of 40 mA, and a 2θ scan range of 5°–60°. FTIR analysis was performed using a FTIR spectrometer (Nicolet 460, Thermo, USA) with a scan range of 500–4000 cm⁻¹. -1 The resolution is 2cm. -1 .

[0046] 1.3 Extraction and culture of HFFs

[0047] With informed consent from the patient, foreskin specimens were collected and immediately rinsed three times with PBS (SH30256.01, HyClone, USA). Subcutaneous adipose tissue and blood vessels were carefully removed with scissors, followed by rinsing three times with PBS containing penicillin-streptomycin (SV30010, Hyclone, USA). The tissue was cut into rectangular strips, and the epidermis was removed with 0.3% dispersin II (10888700, Roche, USA). The remaining dermal tissue was cut into chyme with scissors and thoroughly digested with 0.3% type IV collagenase (17104-019, Gibco, USA). Impurities were then filtered through a 40 μm diameter filter. After centrifugation and resuspension, HFFs were cultured in DMEM / high glucose medium (SH30243.01, HyClone, USA) with 10% fetal bovine serum (SH30070.03, HyClone, USA) and 1% penicillin-streptomycin in preparation for further experiments.

[0048] 1.4 In vitro biocompatibility of composite nanofiber membranes

[0049] After vacuum drying for one week, the composite nanofiber membrane collected on a circular coverslip was sterilized by ultraviolet irradiation for 30 minutes in a biosafety cabinet. In the cytotoxicity experiment, 5 x 10⁻⁶ nanofiber membranes were used... 4 HFFs were seeded on a 24-well composite nanofiber membrane and cultured overnight before the following experiments were performed.

[0050] Live / dead cell staining: Staining solution was prepared at a ratio of 1:1000 using the CalceinAM / PI cytotoxicity and cell viability staining kit (C2015m, Beyotime, China). Live and dead cells were stained separately at 37°C in the dark for 30 min, and then observed under a fluorescence microscope (DMI3000B, Leica, Germany). The number of CalceinAM-positive (live) and PI-positive (dead) cells was counted using Image-proplus 6.0. All experiments were performed independently, with five replicates per group.

[0051] Cytoskeleton staining: Cell morphology on the composite nanofiber membrane was observed on days 1 and 3 of culture. Briefly, the culture medium was removed, the cells were washed three times with PBS, fixed with 4% paraformaldehyde (PFA, 158127-500G, Sigma, Germany) for 20 min, and then perforated with Triton X-100 (T9284-500ML, Sigma, Germany) for 15 min. Cells were stained with phalloidin (1:1000, KM0130, Bio-Lab, China) and DAPI (1:1000, 40728ES03, Yeasen, China). Images were captured using a confocal laser scanning microscope (TSCSP8, Leica, Germany).

[0052] Cell proliferation assay: Cell proliferation was assessed using a cell counting kit-8 (CCK-8, CK04, Dojindo, Japan) after 1, 3, and 5 days of culture. In short, the culture medium was removed and the cells were washed with PBS. The CCK-8 reagent was prepared as a working solution according to the instructions, added to 24-well plates, and incubated for 2 hours. The absorbance at 450 nm was read using a microplate reader (Mμltiskan MK3, Thermo, USA). All experiments were performed in triplicate.

[0053] 1.5 Construction of in vitro AD

[0054] To construct AD in vitro, nanofiber membranes were cut into 15mm diameter circles and placed at the bottom of a 24-well plate, with a 10mm inner diameter steel ring placed on top. 0.5x10 6 1x10 6 3x10 6 and 6x10 6HFFs were seeded into composite nanofiber membranes to construct adenocarcinoma cells (ADs) of varying thicknesses. ADs were cultured for 48 h, then the culture medium was removed, the cells were washed three times with PBS, fixed with 4% PFA for 4 h, and dehydrated using a gradient of ethanol and water. The ADs were then embedded in paraffin, sectioned into 4-6 μm thick pieces, and stained with hematoxylin and eosin (HE, Solarbio, China) to assess the thickness and cell arrangement morphology of the ADs.

[0055] 1.6 modRNA synthesis

[0056] The method for synthesizing modRNA is consistent with our previous reports.

[15] In short, mRNA is synthesized from a linearized DNA template containing universal 5' and 3' URTs and a poly-A tail using T7 RNA polymerase-mediated transcription. During synthesis, uridine is replaced by N1-methylpseudouridine to enhance its in vitro stability and protein translation, hence the term "modRNA". The modRNA is then purified using a purification kit (K0702, Thermo, USA) and treated with phosphorylase (M0289S, NEB, UK) at 37°C for 30 min to remove residual 5' phosphate. After further purification and quantification, the modRNA is resuspended at 1 μg / μl in 10 mM TrisHCl and 1 mM EDTA for later use. Previous studies

[13] It has been identified as GFP, Luciferase, and human VEGFA. 165 Open reading frame sequences for modRNA production are provided.

[0057] 1.7 ModRNA Transfection and Evaluation

[0058] According to the manufacturer's instructions, modRNA was transfected into HFFs using MessengerMAX Lipofectamine (LMRNA015, Invitrogen, USA). The modRNA and MessengerMAX were diluted separately in serum-free Opti-MEM (31985070, Gibco, USA) and incubated at room temperature (RT) for 5 min. They were then mixed and incubated at RT for 15 min to form a liposome-modRNA complex. Cells were transfected with the complex in Opti-MEM for 4 h, after which the transfection medium was replaced with fresh medium. Approximately 1 x 102 cells per well of a 24-well plate were transfected with 2 μg modRNA and 10 μl MessengerMAX per well. 6 HFFs.

[0059] Transfection efficiency was analyzed using modGFP. In short, HFFs transfected with modGFP on AD cells were isolated into single cells using 0.25% trypsin-EDTA (25200072, Gibco, USA) and detected by flow cytometry (FACSCanto™, BD, Germany).

[0060] For modVEGFA transfection, conditioned medium was collected at different time points (4h, 12h, 24h, 48h, 72h, 120h, 1w), and analyzed using ELISA (R&D system) to measure the total content of VEGFA protein and its expression kinetics. All experiments were performed in triplicate in each group.

[0061] 1.8 In vitro angiogenesis and wound healing experiments

[0062] In the tube forming experiment, 1×10 5 HUVECs were inoculated into 48-well plates coated with a matrix gel and cultured in 200 μl of conditioned medium from modLuc or modVEGFA transfected AD. Tube formation was observed and photographed under a microscope every 2 hours after treatment. The number of tubes was counted using Image-proplus 6.0 software. All experiments were performed independently, with 5 replicates per group.

[0063] In the scratch test, 5×10 5 HUVECs were inoculated in 6-well plates and cultured overnight. The fused monolayer of HUVECs was then directly scratched with the tip of a 100 μl sterile pipette, followed by 48 hours of culture in conditioned medium transfected with AD from modLuc or modVEGFA. Images were captured under a microscope at 0 h, 24 h, and 48 h and analyzed using Image-proplus 6.0 software. All experiments were performed independently, with five replicates per group.

[0064] 1.9 Mouse wound healing model and intervention

[0065] Animal care and experiments were conducted in accordance with the guidelines of the Animal Care and Experimentation Committee of Shanghai Children's Medical Center. Six-week-old male nude mice (n=12, 4 per group) were provided by Shanghai Jiesijie Laboratory Animal Co., Ltd. The male nude mice were randomly divided into three groups: a) control group: untreated wounds; b) Sca-Fb... modLuc Group: Cover the wound with modLuc AD; c) Sca-Fb modVEGFAGroup 1: Wounds were covered with AD transfected with modVEGFA. After isoflurane anesthesia, 10 mm diameter mouse skin samples were harvested to establish a full-thickness skin lesion model. Skin wounds in all groups were covered with Tegaderm sterile dressings (3M Healthcare). Photographs were taken immediately postoperatively and every other day until healing. Healing was defined as the time required for complete epithelial cell regeneration and tissue filling of the wound. Wound area was quantified using Image-proplus 6.0.

[0066] 1.10 Immunofluorescence and Histological Staining

[0067] Tissue samples were collected from the lesions and on day 10 post-treatment. The samples were fixed overnight with 4% PFA, dehydrated using a gradient of ethanol and water solutions, and embedded in paraffin to prepare tissue sections. After hydration with a series of gradient ethanol solutions, tissue sections were prepared according to the manufacturer's instructions and stained with hematoxylin-eosin (G1120, Solarbio, China) and trichrome marshmallow stain (G1340, Solarbio, China). The morphology of the wound healing tissues and the survival of Alzheimer's disease (AD) were observed under a microscope.

[0068] Immunohistochemical methods: Paraffin-embedded tissue was cut into 6 μm thick sections and then hydrated with a series of gradient ethanol solutions. Microwave antigen extraction was performed on the hydrated tissue sections in citrate buffer (pH 6.0) (P0081, Beyotime, China). The tissue sections were perforated with 0.2% Triton-X100 for 20 min, blocked with 10% goat serum for 1 h, and labeled with the target protein overnight at 4°C with primary antibody. Then, the sections were stained with Alexa Fluor-488 / 555 conjugated with secondary antibody at RT for 2 h, followed by staining with DAPI (1:1000) at RT for 5 min. The primary antibodies were CD31 (ab182981, Abcam) and Lamin A+C (ab108595 or ab40567, Abcam). The secondary antibody was Alexa Fluor488 conjugated with donkey anti-rabbit IgG H&L (1:1000, ab150073, Abcam). Image recording and data analysis were performed using a confocal laser scanning microscope.

[0069] 1.11 Statistical Analysis

[0070] All data are expressed as mean ± standard deviation. One-way ANOVA and Bonferroni posterior (SPSS 26.0) were used to assess differences between groups. All statistical tests were two-tailed, with a significance level of P < 0.05.

[0071] 2. Experimental Results

[0072] 2.1 Structural characteristics of composite nanofiber membranes

[0073] We obtained various composite nanofiber membranes with different collagen / gelatin / PLCL blend ratios via electrospinning. The microstructure of the material surface and the diameter of the composite nanofibers were obtained through observation and calculation using scanning electron microscopy (SEM) images. Figure 1 As shown, we can observe that all solutions with a PLCL mass fraction of 50% exhibit stable electrospinning without dripping, and no bead-like changes were observed in the SEM images. However, the 0% BC (collagen:gelatin:PLCL = 0:50:50) and 10% BC (collagen:gelatin:PLCL = 10:40:50) groups show slight adhesion. Overall, the diameter of the composite nanofibers in each group is mainly distributed in the range of 200-300 nm, with uniform thickness, smooth surface, and almost no ultrafine or ultracoarse fibers. Furthermore, as the collagen content increases, the diameter distribution curve tends to shift to the right.

[0074] 2.2 Mechanical Properties of Composite Nanofiber Membranes

[0075] Next, we evaluated the mechanical properties of each composite nanofiber membrane under different dry and wet conditions. First, in the dry state, the tensile stress, elongation at break, and Young's modulus of the 0% BC group (without collagen) were 4.79±0.46, 47.1±5.4, and 10.2±0.6, respectively. Figure 2 (A and 2C) With different collagen incorporation ratios, the maximum elongation of the composite nanofiber membranes appeared to change slightly, but the overall change was not significant. However, when the collagen:gelatin:PLCL ratio was 40:10:50, the maximum elongation suddenly increased significantly, with the 50% BC group increasing by 45% compared to the 0% group. Figure 2 A). Except for the 40% group, there was no significant difference in Young's modulus among the groups. Figure 2 B). Furthermore, the maximum elongation of the composite nanofiber membrane in the wet state appears to be exactly the opposite of that in the dry state; compared to the 0% group, the elongation of the 50% BC group decreased by 43%. Figure 2 C). Furthermore, by analyzing Young's modulus, we found that the Young's modulus of the composite nanofiber membrane gradually increased with increasing collagen percentage; compared to the 0% group, the Young's modulus of the 50% BC group increased by 292% (C). Figure 2 D).

[0076] 2.3 XRD and FTIR composition determination of composite nanofiber membranes

[0077] XRD patterns: XRD patterns of PLCL (non-electrospun membrane), collagen powder, gelatin powder, and 5 groups of electrospun nanofibers are shown below. Figure 3As shown in Figure A, neither gelatin nor collagen showed obvious diffraction peaks, while the PLCL material had a Bragg diffraction peak between 16° and 17°. All the blended nanofiber membranes also showed a characteristic peak in this region (around 17°), with the new Bragg diffraction peak of the 50% BC group appearing at 16.4°. This indicates that all electrospun nanofibers are semi-crystalline structures.

[0078] FTIR spectroscopy: To investigate the surface properties of nanofibers, we analyzed the FTIR spectra of all different groups of nanofiber films. Figure 3 B) It was found that gelatin and collagen have similar individual absorption peaks in the ATR-FTIR spectrum, mainly because gelatin is obtained from the hydrolysis of collagen and contains similar amino acid profiles. All five groups of blended nanofibers exhibited similar spectra. They showed similar absorption peaks at 1640 cm⁻¹. -1 (Amide I) and 1545cm -1 Two absorption peaks were observed at (amide II), which are characteristic peaks of collagen or gelatin. Additionally, at 2944 cm⁻¹... -1 and 1758cm -1 Absorption peaks were observed in the blended nanofibers, corresponding to the stretching vibration peaks of the asymmetric CH2 group and ester group (C=O) on the PLCL molecule, respectively.

[0079] 2.4 Biocompatibility of Composite Nanofiber Membranes

[0080] Dead / Live Cell Staining: To investigate the biocompatibility of nanofiber membranes with different collagen and gelatin mixing ratios, we first seeded HFFs onto each group of composite nanofiber membranes, and then used the Calcein AM / PI kit to label dead and live cells, respectively. The results showed that HFFs adhered and stretched well on each group of nanofiber membranes on day 1. Figure 4 A). Quantitative analysis results show ( Figure 4 B) The proportion of live cells exceeded 96%, with only a small number of dead cells, and there was no significant difference in the number of dead cells among the groups.

[0081] Cytoskeleton staining: Results showed ( Figure 5 (Red represents F-actin; blue represents DAPI). HFFs fully extended and exhibited a polygonal cell morphology after 24 hours of inoculation onto the composite nanofiber membrane. Cell density increased with increasing collagen content. After 3 days of culture, cells in the 40% BC and 50% BC groups had completely diffused onto the surface of the nanofiber membrane, and their cells stacked directly on top of each other while maintaining good cell morphology. In summary, all composite nanofiber membranes promoted the adhesion and proliferation of HFFs, and the biocompatibility of the composite nanofiber membranes improved with increasing collagen content.

[0082] CCK8 proliferation experiment: CCK8 detection results of HFFs on nanofiber membranes in each group are as follows: Figure 6 As shown, significant cell proliferation was observed in all groups after 5 days of culture, indicating good biocompatibility of the collagen / gelatin / PLCL composite nanofiber membrane. We also found that cell proliferation in the 50% BC group was significantly superior to other groups on days 1, 3, and 5 after inoculation. The results suggest that collagen / PLCL nanofibers better promote cell adhesion and proliferation compared to gelatin / PLCL nanofibers, possibly because collagen promotes cell proliferation more effectively than gelatin, as evidenced by cytoskeleton staining. Figure 5 This has also been confirmed in [the text].

[0083] 2.5 Construction of artificial dermis in vitro

[0084] Based on the results of scanning electron microscopy, mechanical property analysis, and component determination, a collagen / gelatin / PLCL composite nanofiber membrane (50% BC group), which possesses both good mechanical properties and biocompatibility, was selected as the scaffold material for subsequent research. Therefore, the 50% BC group composite nanofiber membrane was used to construct artificial dermis (AD) in vitro with HFFs. HE staining of AD was as follows... Figure 7 As shown in Figure A, when the cell density is 0.5 x 10⁻⁶... 6 At first, HFFs formed only a single cell membrane on the surface of the composite nanofiber membrane. However, with increasing cell density, 2–3 cell layers could be observed on the surface; at a density of 1.0 x 10⁻⁶. 6 ~6.0x10 6 At that time, a distinctly thick adenomatous scaffold (AD) had already formed, with cells evenly distributed on the scaffold, plump cytoplasm, and intact morphology. Quantitative analysis of AD thickness showed that ( Figure 7 B), 0.5x10 6 1x10 6 3x10 6 and 6x10 6 The densities correspond to thicknesses of 14.8 ± 1.4 μm, 27.1 ± 3.0 μm, 52.1 ± 2.8 μm, and 129.9 ± 11.5 μm. In general, it is feasible to construct ADs of different thicknesses using 50% BC group composite nanofiber membranes containing HFFs.

[0085] 2.6 Efficiency and protein expression of AD transfection with GFP modRNA

[0086] To verify that modRNA can be effectively translated in AD, we first transfected AD with GFP modRNA to observe its expression effect and transfection efficiency. The results showed ( Figure 8A) AD cells began expressing GFP (green fluorescent protein) 4 hours after transfection, with the fluorescence signal intensity peaking at 24 hours post-transfection. At 48 hours post-transfection, the GFP protein signal gradually weakened, but the transfected cells continued to proliferate, and no apoptosis was observed, indicating that the transfection had almost no cytotoxic effect on the cells. Flow cytometry analysis showed ( Figure 8 B) 24 hours after transfection, the efficiency of modRNA transfection of AD was as high as 88%.

[0087] 2.7 Secretion of AD after VEGFA modRNA transfection

[0088] To determine the secretion kinetics of AD transfected with VEGFA modRNA, we transfected AD with VEGFA modRNA to induce VEGFA protein overexpression, and used ELISA to detect the new and cumulative secretion of VEGFA protein at different time points (4h, 12h, 24h, 48h, 72h, 120h, and 168h). The results showed that in the first 3 days after transfection, Fb... modVEGF The secretion level of newly added VEGFA protein in the control group was significantly higher than that in the control group. Figure 9 A). Analysis of the cumulative secretion of VEGFA protein revealed ( Figure 9 B), Fb modVEGF The levels in the control group were significantly higher than those in the control group at all assessment time points, and the VEGFA protein level stabilized on day 3 post-transfection.

[0089] 2.8 VEGFA modRNA transfection of AD promotes HUVECs to form tubes in vitro.

[0090] To further confirm the functionality of the VEGFA protein secreted by AD cells modified with VEGFA modRNA, we tested whether its conditioned medium promoted angiogenesis in human umbilical vein cells (HUVECs) in vitro. The results of the angiogenesis assay showed that ( Figure 10 Compared to the Control group, using Fb modVEGF The conditioned medium induced a significant increase in tubular structures in the group.

[0091] 2.9 VEGFA modRNA transfection of AD promotes the proliferation and migration of HUVECs in vitro.

[0092] Furthermore, in the HUVECs scratch test, we also observed that, compared with the Control group, from Fb modVEGF The conditioned medium extracted from the group significantly promoted the proliferation and migration of HUVECs. Figure 11 ).

[0093] 2.10 Wound healing in mice

[0094] This study used a mouse full-thickness skin excision wound model to evaluate AD(Sca-Fb) transfected with VEGFAmodRNA. modVEGF Group), AD (Sca-Fb) transfected with Luciferase modRNA modLuc The wound healing ability of the control group and the untreated group (AD group) was compared. Full-thickness skin was removed from nude mice, and the wound was then covered with AD as described above (wound diameter 1 cm, the same size as the AD). Gross images of each group on days 0, 4, and 10 post-treatment are shown below. Figure 12 As shown in Figure A. At each observation time point, Sca-Fb modVEGF The wound healing rate in the Control group was higher than that in the other two groups. Four days after treatment, the wound healing rates in the Sca-Fb group were significantly higher. modLuc Group and Sca-Fb modVEGF The wound area in the groups decreased to 60.4±6.5%, 50.8±3.2%, and 29.8±4.8%, respectively. Figure 12 B). On day 10 of treatment, the wounds in the Sca-FbmodVEGF group were almost completely healed (down to approximately 1.7%).

[0095] 2.11 Morphological staining of healed wounds

[0096] To assess histopathological changes and regenerative capacity after AD treatment, we performed HE staining and Masson staining on tissue sections from each group of wounds and normal skin specimens on day 10 post-treatment. Figure 13 As shown. Normal skin tissue consists of the epidermis, dermis, subcutaneous fat, and hair follicles. On the 10th day after wound treatment, Sca-Fb modVEGF The control group showed the best wound healing and formed arteries with complete vascular morphology. (The control group and Sca-Fb...) modLuc The group still had varying degrees of skin tissue damage, with obvious granulation tissue at the wound attachment site, and a large number of inflammatory cells and fibroblasts aggregated. Figure 13 A). Furthermore, we can obtain information from Masson staining results ( Figure 13 In B), it was observed that collagen fiber bundles in the subcutaneous dermis of natural skin were loosely and orderly arranged in a wavy pattern. In healed wounds, the subcutaneous collagen fiber bundles were significantly reduced and disordered. We also found Sca-Fb modVEGF The group contained intact and relatively large AD cells beneath the epidermis. The host fibroblasts beneath the AD cell layer were well-arranged, with abundant collagen fibers. These data suggest that modifying AD with VEGFA modRNA improves graft survival, thereby promoting wound healing.

[0097] 2.12 Survival rate of artificial dermis after in vivo transplantation

[0098] The survival of subepidermal transplanted cells is crucial for maintaining the morphology of healed wounds. Therefore, we first assessed the survival rate of HFFs in AD using immunofluorescence staining. Figure 14 As shown in Figure A, no AD cells (human fibroblasts) were detected in the Control group, while some cells survived in the other two groups. (Sca-Fb) modVEGF The subepidermal AD cells in the group were evenly distributed, and the number of surviving cells was significantly higher than that in the Sca-Fb group. modLuc Group( Figure 14 B).

[0099] 2.13 Angiogenesis in the wound healing area

[0100] To further evaluate the ability of VEGFAmodRNA-modified AD to stimulate angiogenesis in the wound healing area, we performed CD31 staining and analysis. The results showed that ( Figure 15 Compared with other groups, Sca-Fb modVEGF The group had a greater number of new blood vessels, and the vessels were round, indicating that its new blood vessels were more stable and mature.

[0101] References

[0102] [1]Wang PH, Huang BS, Horng HC, et al. Wound healing. J Chin MedAssoc.2018;81(2):94-101.

[0103] [2]Han G,Ceilley R.Chronic Wound Healing:A Review of CurrentManagement and Treatments.Adv Ther.2017;34(3):599-610.

[0104] [3] Nourian DA, Mirahmadi BF, Chehelgerdi M, et al. Skin tissue engineering: wound healing based on stem-cell-based therapeutic strategies. Stem Cell Res Ther. 2019; 10(1): 111.

[0105] [4]Martin P,Nunan R.Cellular and molecular mechanisms of repair inacute and chronic wound healing.Br J Dermatol.2015;173(2):370-378.

[0106] [5]Chaudhari AA,Vig K,Baganizi DR,et al.Future Prospects forScaffolding Methods and Biomaterials in Skin Tissue Engineering:A Review.IntJ MolSci.2016;17(12):1974.

[0107] [6]Amirsadeghi A,Jafari A,Eggermont LJ,et al.Vascularizationstrategies for skin tissue engineering[J].Biomaterials Science,2020,8(15):4073–4094.

[0108] [7]Madeddu P.Therapeutic angiogenesis and vasculogenesis for tissueregeneration[J].Experimental Physiology,2005,90(3):315–326.

[0109] [8]Jahani M,Rezazadeh D,Mohammadi P,et al.Regenerative medicine andangiogenesis;challenges and opportunities[J].Advanced PharmaceuticalBulletin,2020,10(4):490–501.

[0110] [9]Sahin U,Kariko K,Tureci O.Mrna-based therapeutics--developing anew class of drugs.Nature reviews.Drug discovery.2014;13:759-780.

[0111]

[10] Lui KO,Zangi L,Silva EA,et al.Driving vascular endothelial cellfate of human multipotent isl1+ heart progenitors with VEGFA modifiedmrna.Cell research.2013;23:1172-1186.

[0112]

[11] Warren L,Manos PD,Ahfeldt T,et al.Highly efficient reprogrammingto pluripotency and directed differentiation of human cells with syntheticmodified mrna.Cell stem cell.2010;7:618-630.

[0113]

[12] Kormann MS,Hasenpusch G,Aneja MK,et al.Expression of therapeuticproteins after delivery of chemically modified mrna in mice.Naturebiotechnology.2011;29:154-157.

[0114]

[13] Zangi L,Lui KO,von Gise A,et al.Modified mrna directs the fate ofheart progenitor cells and induces vascular regeneration after myocardialinfarction.Nature biotechnology.2013;31:898-907.

[0115]

[14] Zangi L, Oliveira S, Ye Y, et al. Insulin-like growth factor 1receptor dependent pathway drives epicardial adipose tissue formation after myocardial injury. Circulation. 2017; 135:59-72.

[0116]

[15] Yu Z, Witman N, Wang W, et al. Cell-mediated delivery of VEGFAmodified mRNA enhances blood vessel regeneration and ameliorates murinecritical limb ischemia. J Control Release. 2019; 310:103-114.

[0117] The embodiments described above are some, but not all, of the embodiments of this application. The detailed description of the embodiments of this application is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.

Claims

1. An artificial skin graft, characterized in that, The artificial skin graft has a nanofiber membrane as its substrate, which is loaded with fibroblasts transfected with modRNA, specifically VEGFA modRNA. The nanofiber membrane is a composite nanofiber membrane made of collagen, gelatin, and poly(L-lactide-caprolactone) in a mass ratio of 40:10:

50. The composite nanofiber membrane is prepared by electrospinning.

2. The artificial skin graft according to claim 1, characterized in that, The fibroblasts mentioned are human foreskin fibroblasts.

3. The method for preparing the artificial skin graft according to claim 1 or 2, characterized in that, Includes the following steps: A) Preparation of nanofiber membranes; B) Seed fibroblasts into the nanofiber membrane and culture them; C) Perform modRNA transfection.

4. The use of the artificial skin graft of claim 1 or 2 in the preparation of a product for repairing wounds caused by acute or chronic skin injuries.

Citation Information

Patent Citations

  • Skin substitute for automatically capturing endothelial progenitor cells and promoting vascularization and construction method thereof

    CN101985052A